Considerations in the development and organisation of public and non-profit respite care services for persons with intellectual disability in South Africa: a mixed method study - Abrahams, Toni (Department of Psychiatry and Mental Health, 2025)
Background: Family caregiving, whilst rewarding, in the context of limited support can also negatively impact caregivers, families and persons with intellectual disability. Respite care, a disability support service, offers an avenue to support this population. However, in South Africa, the extent and nature of respite care provision is unclear. This study aimed to address this gap, by finding evidence for how best to organise and develop contextually appropriate respite care services for persons with intellectual disability in South Africa. Method: This mixed method, pragmatic and inclusive study was guided by the Human Rights-based approach, the Health System Dynamics model and Evans's model of respite care. Four sub-studies were triangulated and integrated: a scoping review of global respite care models, principles and practices; a policy analysis of relevant legislation and policies in South Africa; a national survey of respite care services; and interviews with respite care service providers, family caregivers, persons with intellectual disability, and key informants from the disability, health and social sectors. Results: Contextual considerations, exacerbating this population's challenges in South Africa, included the need for improved formal services, having to address continued institutionalisation of persons with intellectual disability, improving informal support, considering cultural beliefs, addressing stigma and discrimination, factoring in poverty and care costs and safety concerns. This necessitates improved provision of state-funded respite care for persons with ID and their families which is needs-, support- and rights-based, culturally sensitive, and more available, accessible, affordable, equitable and responsive, and of good quality. Addressing stigma and poor understanding of intellectual disability and respite care through training, awareness, advocacy and self-advocacy in public policy and practice is crucial. Shared terminology, inclusive definitions and better service information is required, as is utilising rights-based principles and practices, where innovation and adapting existing respite care practices can add to the local evidence base. Leadership and governance considerations highlight the need to address disability and respite care legislative and policy gaps, using a twin-track approach, where rights-based governance can support better collaboration and inclusive consultation between all stakeholders, supporting access to respite care across the lifespan. Funding considerations include the need for adequate respite care funding supported by funding models and alternative funding mechanisms which enhance respite care provision in communities. This can be supported by ID-disaggregated data to inform state efforts, and exploration of respite care's potential cost-effectiveness. Equitable access necessitates accessible infrastructure, activities, and adequate supplies, requiring consideration of different types of respite care, public-private partnerships and improved general physical and informational accessibility. Human resource considerations include a focus on staff support, supervision and training, circumspect reliance on volunteers, enlisting experts by experience and drawing on the pool of intersectoral human resources. Service delivery considerations highlight the need for a wider range of person- and family-centred respite care services, including more in-home respite care services and out-of-home respite care service options. These services should offer flexible service packages based on needs-assessments, with meaningful activities, relying on service evaluations for improvements and establishing outcomes, and fostering good provider-client partnerships. By addressing these considerations, the benefits of respite care can potentially support improved health, wellbeing and social protection of persons with intellectual disability, their caregivers and families, affording benefit to this population and beyond. Conclusion: These considerations for improving respite care in South Africa for persons with intellectual disability, can help to sustain and develop services. This necessitates improvements in several areas, supported by a rights-based approach, and requiring concerted advocacy and self-advocacy efforts. The study adds to the respite care evidence base and points to further areas of enquiry to enhance the evidence base for low- and middle-income countries.